Secondary battery and electric device
By designing a multi-layer active material structure and carbon coating mechanism in the positive electrode sheet of the secondary battery, the problem of insufficient circulation and storage performance of the existing secondary battery is solved, and higher battery performance is achieved.
Patent Information
- Application Number
- CN202410396414.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-02
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-04-02
AI Technical Summary
Existing secondary batteries have shortcomings in circulation performance and storage performance, and it is difficult to meet the high-demand application needs.
A secondary battery is designed, wherein the positive electrode sheet comprises two layers of active material areas: a first area close to the current collector and a second area away from the current collector. The first active material in the first region has a higher carbon layer mass content, the second active material in the second region has a lower carbon layer mass content, and oxides are added to each region to absorb acidic by-products.
By optimizing the distribution of active materials and carbon coating, the wetting performance of the electrolyte is improved, and the possibility of transition metal dissolution in the active materials is reduced, thereby significantly improving the cycling performance and storage performance of the battery.
Smart Images

Figure CN119852538A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery and an electrical device. Background Art
[0002] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. However, as the application of secondary batteries becomes more and more extensive, people's requirements for the cycle performance and storage performance of secondary batteries are also getting higher and higher. How to develop a secondary battery with good cycle performance and storage performance is still a problem that technicians need to solve urgently. Summary of the invention
[0003] The present application is made in view of the above-mentioned problems, and its object is to provide a secondary battery and an electric device, wherein the secondary battery has cycle performance and storage performance.
[0004] A first aspect of the present application provides a secondary battery, comprising a positive electrode plate, the positive electrode plate comprising a positive electrode current collector and a positive electrode film layer formed on at least one surface of the positive electrode current collector, the positive electrode film layer having a first surface away from the positive electrode current collector and a second surface arranged opposite to the first surface, the thickness of the positive electrode film layer is denoted as H, the region within a thickness range from the second surface of the positive electrode film layer to 0.1H is denoted as the first region of the positive electrode film layer, the region within a thickness range from the first surface of the positive electrode film layer to 0.1H is denoted as the second region of the positive electrode film layer, the first region comprises a first active material, the second region comprises a second active material, the first active material comprises a first matrix material and a first carbon layer coated on the surface of the first matrix material, the second active material comprises a second matrix material and a second carbon layer coated on the surface of the second matrix material, and the mass content of the first carbon layer in the first active material is greater than the mass content of the second carbon layer in the second active material.
[0005] The mass content of the first carbon layer in the first active material is controlled to be greater than the mass content of the second carbon layer in the second active material, so that the first active material in the first region close to the current collector has better electrolyte wetting performance than the second active material in the second region far away from the current collector, thereby improving the electrolyte wetting performance of the inner layer of the positive electrode film layer, which is beneficial to improving the electrolyte wetting performance of the overall film layer, and is beneficial to improving the cycle performance and storage performance of the battery. At the same time, carbon coating the active material can reduce the possibility of transition metal dissolution in the active material, improve the conductivity and kinetic properties of the active material, and is beneficial to improving the cycle performance and storage performance of the battery.
[0006] In any embodiment, the mass content of the first carbon layer in the first active material is 2%-4%.
[0007] The mass content of the first carbon layer in the first active material is within a suitable range, which ensures that the first region has excellent electrolyte wettability while preventing excessive coated carbon from affecting the gram capacity of the active material.
[0008] In any embodiment, the mass content of the second carbon layer in the second active material is 0%-1.9%.
[0009] The mass content of the second carbon layer in the second active material is within a suitable range, which ensures that the second region has excellent electrolyte wettability while preventing excessive coated carbon from affecting the gram capacity of the active material.
[0010] In any embodiment, the first region includes a first oxide, the second region includes a second oxide, and the first oxide and the second oxide each independently include one or more of Al2O3, MgO, TiO2, ZrO2, Y2O3, CaO, MnO2, and NiO.
[0011] The secondary battery satisfies: X%>Y%,
[0012] Wherein, X% is the mass content of the first oxide, based on the total mass of the first active material and the first oxide in the first region;
[0013] Y% is the mass content of the second oxide based on the total mass of the second active material and the second oxide in the second region.
[0014] The carbon coating on the surface of the positive electrode active material is conducive to the adsorption and fixation of the electrolyte, which is conducive to improving the electrolyte wettability of the film layer. However, the surface coated carbon is also easy to absorb trace water in the preparation environment, so that there will be trace water in the positive electrode film layer. These trace water will further react with the electrolyte to generate acidic byproducts. The acidic byproducts will corrode the positive electrode active material and affect the cycle performance and storage performance of the battery. As mentioned above, in order to improve the electrolyte wettability of the first region close to the current collector, the carbon content of the first active material in the first region will be higher than the carbon content of the second active material in the second region, so the water content in the first region may be higher than the water content in the second region.
[0015] The present application adds a first oxide in the first region and a second oxide in the second region. On the one hand, the first oxide and the second oxide act as acid capture additives to absorb acidic byproducts produced by the reaction of trace water with the electrolyte, thereby reducing the impact of trace water introduced by carbon coating. On the other hand, because the water content in the first region may be higher than the water content in the second region, there will be more acidic byproducts in the first region. Controlling the mass content of the first oxide in the first region to be greater than the mass content of the second oxide in the second region can better solve the technical problem of trace water introduced by coated carbon, and can effectively improve the cycle performance and storage performance of the battery.
[0016] In any embodiment, based on the total mass of the first active material and the first oxide in the first region, the mass content X% of the first oxide is 0.030%-1.0%.
[0017] In any embodiment, based on the total mass of the first active material and the first oxide in the first region, the mass content X% of the first oxide is 0.030%-0.6%.
[0018] The mass content of the first oxide is controlled within an appropriate range to ensure that the acidic byproducts in the first region are removed by the first oxide to the greatest extent, thereby reducing the impact of the acidic byproducts on the positive electrode active material and also reducing the impact of the first oxide on the energy density of the battery.
[0019] In any embodiment, based on the total mass of the second active material and the second oxide in the second region, the mass content Y% of the second oxide is 0%-0.5%.
[0020] In any embodiment, based on the total mass of the second active material and the second oxide in the second region, the mass content Y% of the second oxide is 0% to 0.3%.
[0021] The mass content of the second oxide is controlled within an appropriate range to ensure that the acidic byproducts in the second region are removed by the second oxide to the greatest extent, thereby reducing the impact of the acidic byproducts on the positive electrode active material and also reducing the impact of the second oxide on the energy density of the battery.
[0022] In any embodiment, a mass ratio of the sum of the mass of the first active material and the first oxide to the sum of the mass of the second active material and the second oxide is 1:9-9:1.
[0023] By controlling the mass ratio of the sum of the masses of the first active material and the first oxide to the sum of the masses of the second active material and the second oxide within an appropriate range, it is possible to take into account both the electrolyte wettability of the positive electrode film layer and the average gram capacity of the active material, thereby comprehensively improving the cycle performance and energy density of the battery.
[0024] In any embodiment, the first matrix material and the second matrix material each independently include one or more of a layered oxide material, a spinel lithium manganese oxide material, a phosphate material, and modified forms of any of the foregoing substances, wherein the modified forms include one or more of doping modification and coating modification.
[0025] In any embodiment, the first matrix material and the second matrix material both include lithium iron phosphate.
[0026] In any embodiment, the volume distribution particle size Dv50 of the first active material is 0.5 μm-2.0 μm; and / or the volume distribution particle size Dv50 of the second active material is 0.5 μm-2.0 μm.
[0027] In any embodiment, the volume distribution particle size Dv50 of the first active material is 0.8 μm-1.5 μm; and / or the volume distribution particle size Dv50 of the second active material is 0.8 μm-1.5 μm.
[0028] In any embodiment, it is characterized in that the specific surface area of the first active material is 8m 2 / g-16m 2 / g; and / or, the specific surface area of the second active material is 9m 2 / g-15m 2 / g.
[0029] In any embodiment, the mass content of the second carbon layer in the second active material is 0.5%-1.9%.
[0030] In any embodiment, the mass content of the second carbon layer in the second active material is 0.7%-1.7%.
[0031] Coating the surface of the lithium iron phosphate material in the second region with a suitable amount of carbon can improve the conductivity and kinetic properties of the lithium iron phosphate material, increase the gram capacity of the material, and facilitate obtaining a battery with a high energy density.
[0032] In any embodiment, the coating area density of the positive electrode film layer is 0.26g / 1540.25mm 2 -0.45g / 1540.25mm 2 .
[0033] The positive electrode film layer has a high coating surface density, which is beneficial to improving the energy density of the battery. At the same time, the aforementioned multi-layer design can also solve the technical problem of poor wettability of the inner layer of the electrode when the coating surface density is large, and can improve the cycle performance and storage performance of high energy density batteries.
[0034] A second aspect of the present application provides an electrical device, comprising the secondary battery described in the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic diagram of one embodiment of the positive electrode plate of the present application.
[0036] Figure 2 It is a schematic diagram of another embodiment of the positive electrode plate of the present application.
[0037] Figure 3 It is a schematic diagram of another embodiment of the positive electrode plate of the present application.
[0038] Figure 4 It is a schematic diagram of one embodiment of the secondary battery of the present application.
[0039] Figure 5 It is an exploded schematic diagram of one embodiment of the secondary battery of the present application.
[0040] Figure 6 It is a schematic diagram of an embodiment of a battery module of the present application.
[0041] Figure 7 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0042] Figure 8 yes Figure 7 An exploded schematic diagram of an embodiment of a battery pack is shown.
[0043] Fig. 9 It is a schematic diagram of one embodiment of an electric device including the secondary battery of the present application as a power source.
[0044] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 secondary battery, 51 shell, 52 electrode assembly, 53 cover plate, 10 positive electrode sheet, 101 positive electrode current collector, 102 positive electrode film layer, 102a first surface, 102b second surface, 1021 first region, 1022 second region, 1023 middle region. DETAILED DESCRIPTION
[0045] Below, the embodiments of the positive electrode slurry, preparation method, positive electrode sheet, secondary battery and electric device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0046] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0047] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0048] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0049] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0050] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0051] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0052] At present, electric vehicles have an increasing demand for the energy density of power batteries. The more positive electrode active materials are loaded in the effective space of the battery, the higher the energy density will be. One of the effective improvement directions is to increase the coating surface density of the positive electrode film layer, thereby increasing the energy density of the battery. However, increasing the surface density of the film layer will cause the positive electrode film layer to become thicker or the porosity in the positive electrode film layer to become lower. The increase in the thickness of the membrane and the decrease in the porosity will lead to a decrease in the infiltration ability of the electrolyte, which will have an adverse effect on the cycle performance and storage performance of the battery.
[0053] Based on this, the present application provides a secondary battery, including a positive electrode sheet, such as Figures 1 to 3As shown, the positive electrode plate 10 includes a positive electrode collector 101 and a positive electrode film layer 102 formed on at least one surface of the positive electrode collector 101, the positive electrode film layer 102 has a first surface 102a away from the positive electrode collector 101 and a second surface 102b arranged opposite to the first surface 102a, the thickness of the positive electrode film layer 102 is recorded as H, the area within the thickness range from the second surface 102b of the positive electrode film layer to 0.1H is recorded as the first area 1021 of the positive electrode film layer, and the area within the thickness range from the first surface 102a of the positive electrode film layer to 0.1H is recorded as the second area 1022 of the positive electrode film layer. The thickness H of the positive electrode film layer refers to the thickness of the positive electrode film layer located on a single side of the positive electrode current collector, the first region includes a first active material, the second region includes a second active material, the first active material includes a first matrix material and a first carbon layer coated on the surface of the first matrix material, the second active material includes a second matrix material and a second carbon layer coated on the surface of the second matrix material, and the mass content of the first carbon layer in the first active material is greater than the mass content of the second carbon layer in the second active material.
[0054] like Figures 1 to 3 As shown, the positive electrode film layer 102 further includes a middle region 1023 located between the first region 1021 of the positive electrode film layer and the second region 1022 of the positive electrode film layer and having a thickness of 0.8H (H represents the thickness of the positive electrode film layer 102).
[0055] In some embodiments, the intermediate region includes the first active material and / or the second active material. Figure 2 As shown, the middle region 1023 may be the same as the first region 1021 in composition, whereby the distribution area of the active material in the first region in the thickness direction of the positive electrode film layer 102 is within the thickness range from the second surface 102b of the positive electrode film layer to 0.9H; or Figure 3 As shown, the middle region 1023 may be the same as the second region 1022 in composition, whereby the distribution area of the active material in the second region in the thickness direction of the positive electrode film layer 102 is within the thickness range from the first surface 102a of the positive electrode film layer to 0.9H; or Figure 1 As shown, the middle region 1023 includes the first active material in the first region and the second active material in the second region. At this time, the middle region 1023 includes a layer structure having the first active material in the first region and a layer structure having the second active material in the second region. The above two layer structures may also have a layer interface.
[0056] The mass content of the carbon layer in the positive electrode active material in different regions can be tested by methods commonly used in the art, such as infrared absorption method, specifically, the sample to be tested is burned in an oxygen flow to generate CO2. Since the energy of infrared rays absorbed by CO2 is proportional to its concentration under a certain pressure, the mass content of the carbon layer can be calculated based on the energy change of the CO2 gas before and after passing through the infrared absorber.
[0057] In some embodiments, a mass content of the first carbon layer in the first region in the first active material is greater than a mass content of the second carbon layer in the second region in the second active material.
[0058] As mentioned above, while increasing the compaction density or surface density of the positive electrode film layer, it will affect the wettability of the electrolyte to the active material, especially for the first region close to the current collector. On the one hand, the electrolyte infiltration path is long, and on the other hand, the increased compaction density leads to a decrease in porosity and poor electrolyte infiltration, which deteriorates the cycle performance and storage performance of the first region.
[0059] The carbon layer on the surface of the material has good liquid absorption and retention capabilities, and the mass content of the first carbon layer in the first active material is controlled to be greater than the mass content of the second carbon layer in the second active material, so that the first active material in the first region close to the current collector has a better ability to absorb and lock the electrolyte than the second active material in the second region far away from the current collector. The active material in the first region has a better electrolyte wetting performance, which is beneficial to improving the electrolyte wetting performance of the overall film layer, and is beneficial to improving the cycle performance and storage performance of the battery. At the same time, carbon coating the active material can reduce the possibility of transition metal dissolution in the active material, improve the conductivity and kinetic properties of the active material, and is beneficial to improving the cycle performance and storage performance of the battery.
[0060] In some embodiments, the mass content of the first carbon layer in the first active material is 2%-4%, optionally 2%-3.5%. In some embodiments, the mass content of the first carbon layer in the first active material can be 2%, 2.5%, 3%, 3.5%, 4% or any range therebetween.
[0061] The mass content of the first carbon layer in the first active material is within a suitable range, which ensures that the first region has excellent electrolyte wettability while preventing excessive coated carbon from affecting the gram capacity of the active material.
[0062] In some embodiments, the mass content of the second carbon layer in the second active material is 0%-1.9%. In some embodiments, the mass content of the second carbon layer in the second active material can be 0%, 0.5%, 1%, 1.5%, 1.9% or any range therebetween.
[0063] The mass content of the second carbon layer in the second active material is within a suitable range, which ensures that the second region has excellent electrolyte wettability while preventing excessive coated carbon from affecting the gram capacity of the active material.
[0064] In some embodiments, the first region includes a first oxide, and the second region includes a second oxide, wherein the first oxide and the second oxide each independently include one or more of Al2O3, MgO, TiO2, ZrO2, Y2O3, CaO, MnO2, and NiO.
[0065] The secondary battery satisfies: X%>Y%,
[0066] Wherein, X% is the mass content of the first oxide, based on the total mass of the first active material and the first oxide in the first region;
[0067] Y% is the mass content of the second oxide based on the total mass of the second active material and the second oxide in the second region.
[0068] The carbon coating on the surface of the positive electrode active material is conducive to the adsorption and fixation of the electrolyte, and is conducive to improving the electrolyte wettability of the film layer. However, the surface coated carbon easily absorbs trace water in the preparation environment, so that there will be trace water in the positive electrode film layer. These trace waters will cause the electrolyte to further react to generate acidic byproducts. The acidic byproducts will corrode the positive electrode active material and affect the cycle performance and storage performance of the battery. As mentioned above, in order to improve the electrolyte wettability of the first region close to the current collector, the carbon content of the first active material in the first region will be higher than the carbon content of the second active material in the second region, so the water content in the first region may be higher than the water content in the second region.
[0069] In the present application, a first oxide is added to the first region and a second oxide is added to the second region. On the one hand, the first oxide and the second oxide act as acid capture additives to absorb acidic byproducts produced by the reaction of trace water with the electrolyte, thereby reducing the impact of trace water introduced by carbon coating on the positive electrode active material. On the other hand, because the water content in the first region may be higher than the water content in the second region, there will be more acidic byproducts in the first region. Controlling the mass content of the first oxide in the first region to be greater than the mass content of the second oxide in the second region can better solve the technical problem of trace water introduced by coated carbon, and can effectively improve the cycle performance and storage performance of the battery.
[0070] In some embodiments, based on the total mass of the first active material and the first oxide in the first region, the mass content X% of the first oxide is 0.030%-1.0%, and optionally 0.030%-0.6%.
[0071] In some embodiments, based on the total mass of the first active material and the first oxide in the first region, the mass content X% of the first oxide may be 0.030%, 0.100%, 0.150%, 0.200%, 0.250%, 0.300%, 0.400%, 0.500%, 0.600%, 0.700%, 0.800%, 0.900%, 1.0% or any numerical range therebetween.
[0072] The mass content of the first oxide is controlled within an appropriate range to ensure that the acidic byproducts in the first region are removed by the first oxide to the greatest extent, thereby reducing the impact of the acidic byproducts on the positive electrode active material and also reducing the impact of the first oxide on the energy density of the battery.
[0073] In some embodiments, based on the total mass of the second active material and the second oxide in the second region, the mass content Y% of the second oxide is 0%-0.5%, and optionally 0%-0.3%.
[0074] In some embodiments, based on the total mass of the second active material and the second oxide in the second region, the mass content Y% of the second oxide may be selected as 0%, 0.005%, 0.015%, 0.100%, 0.200%, 0.300%, 0.400%, 0.500% or any numerical range therebetween.
[0075] The mass content Y% of the second oxide is controlled within an appropriate range to ensure that the acidic by-products in the second region are removed by the second oxide to the greatest extent, thereby reducing the impact of the acidic by-products on the positive electrode active material. At the same time, it is also necessary to reduce the impact of the second oxide on the energy density of the battery.
[0076] In some embodiments, the mass ratio of the sum of the mass of the first active material and the first oxide to the sum of the mass of the second active material and the second oxide is 1:9-9:1, optionally 3:7-8:2, and more optionally 5:5-7:3. In some embodiments, the mass ratio of the sum of the mass of the first active material and the first oxide to the sum of the mass of the second active material and the second oxide is 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, or any range therebetween.
[0077] By controlling the mass ratio of the sum of the masses of the first active material and the first oxide to the sum of the masses of the second active material and the second oxide within an appropriate range, it is possible to take into account both the electrolyte wettability of the positive electrode film layer and the average gram capacity of the active material, thereby comprehensively improving the cycle performance and energy density of the battery.
[0078] In some embodiments, the first matrix material and the second matrix material each independently include one or more of a layered oxide material, a spinel lithium manganese oxide material, a phosphate material, and modified forms of any of the foregoing substances, wherein the modified forms include one or more of doping modifications and coating modifications.
[0079] In some embodiments, the layered oxide material includes one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese-based materials.
[0080] In some embodiments, the phosphate material includes one or more of lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, and lithium nickel phosphate.
[0081] In this article, doping modification refers to doping the modified elements into the material body, and coating modification refers to making the modified elements exist in the form of a coating layer on the surface of the material body. The modified elements include one or more of Na, K, Ca, Ba, Sb, Ti, Zr, W, Sr, Nb, Mo, Si, Mg, B, Cr, Ta, Y, Sr, La, Mn, Ni, S, P, and F.
[0082] In some embodiments, the first matrix material and the second matrix material each independently include a layered oxide material, a spinel lithium manganese oxide material, and one or more modified forms of any of the foregoing substances, wherein the modified form includes one or more of doping modification and coating modification.
[0083] In some embodiments, the mass content of the second carbon layer in the second active material is 0%.
[0084] When the first matrix material or the second matrix material adopts one or more of layered oxide materials, spinel lithium manganese oxide materials and modified forms of any of the foregoing substances, the above materials themselves have good conductivity, and the second active material is located in the second region away from the current collector, and the electrolyte has good wettability to it. If the second active material is not carbon-coated, it will not have a significant impact on the wettability of the electrolyte. On the contrary, not carbon-coating will increase the gram capacity of the second active material, so that a battery with high energy density and excellent cycle performance can be obtained.
[0085] In some embodiments, the first matrix material and the second matrix material both include lithium iron phosphate.
[0086] Lithium iron phosphate has the advantage of a long cycle life, and the use of lithium iron phosphate as a matrix material is conducive to constructing a battery with a long cycle life.
[0087] In some embodiments, the volume distribution particle size Dv50 of the first active material is 0.5 μm-2 μm, and can be 0.8 μm-1.5 μm. In some embodiments, the volume distribution particle size Dv50 of the first active material can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.5 μm, 2.0 μm, or any range therebetween.
[0088] In some embodiments, the volume distribution particle size Dv50 of the second active material is 0.5 μm-2.0 μm, and can be 0.8 μm-1.5 μm. In some embodiments, the volume distribution particle size Dv50 of the second active material can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.5 μm, 2.0 μm, or any range therebetween.
[0089] The volume distribution particle size Dv50 of the first active material refers to the meaning known in the art, indicating the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured using instruments and methods known in the art. For example, it can be conveniently measured using a laser particle size analyzer with reference to GB / T 19077-2016 particle size distribution laser diffraction method. The test instrument can be the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK. The definition and test of the volume distribution particle size Dv50 of the second active material refer to the definition and test of the volume distribution particle size Dv50 of the first active material.
[0090] The first active material and the second active material have a suitable volume distribution particle size Dv50, which is beneficial to increase the active sites on the surface of the active material, shorten the ion diffusion path, and increase the gram capacity of the material. At the same time, it also reduces the possibility of side reactions in the electrolyte on the surface of the active material caused by the material's too small particle size and too large specific surface area.
[0091] In some embodiments, the specific surface area of the first active material is 8 m 2 / g-16m 2 In some embodiments, the specific surface area of the first active material may be 8 m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g or any range of values between them.
[0092] In some embodiments, the specific surface area of the second active material is 9 m 2 / g-15m 2 In some embodiments, the specific surface area of the second active material may be 9 m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g or any range of values between them.
[0093] The specific surface area of the first active material can be tested by methods known in the art. As an example, referring to GB / T 19587-2017, the specific surface area analysis test method of nitrogen adsorption is used for testing, and the specific surface area is calculated by the BET (Brunauer Emmett Teller) method. The testing instrument can be the Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA. The definition and test of the specific surface area of the second active material refer to the definition and test of the specific surface area of the first active material.
[0094] Controlling the specific surface area of the first and second active materials within a suitable range is beneficial to increasing the active sites on the material surface and increasing the specific capacity of the material. It is also beneficial to reducing the side reactions between the active materials and the electrolyte and improving the cycle performance and storage performance.
[0095] In some embodiments, the mass content of the second carbon layer in the second active material is 0.5%-1.9%, and optionally 0.7%-1.9%.
[0096] Coating the surface of the lithium iron phosphate material in the second region with a suitable amount of carbon can improve the wetting ability of the electrolyte to the second region, and can also improve the conductivity and kinetic properties of the lithium iron phosphate material, increase the gram capacity of the material, and facilitate obtaining a high energy density battery.
[0097] In some embodiments, the coating area density of the positive electrode film layer is 0.26 g / 1540.25 mm 2 -0.45g / 1540.25mm 2 .
[0098] In some embodiments, the coating area density of the positive electrode film layer can be selected to be 0.26g / 1540.25mm 2 , 0.28g / 1540.25mm 2 , 0.30g / 1540.25mm 2 ,
[0099] 0.32g / 1540.25mm 2 , 0.34g / 1540.25mm 2 , 0.36g / 1540.25mm 2 ,
[0100] 0.38g / 1540.25mm 2 , 0.40g / 1540.25mm 2 , 0.42g / 1540.25mm 2 , 0.44g / 1540.25mm 2 , 0.45g / 1540.25mm 2 Or any range of values in between.
[0101] It should be noted that the coating surface density of the positive electrode film layer in the present application refers to the coating surface density of the positive electrode film layer arranged on one side of the positive electrode current collector.
[0102] The coating surface density of the positive electrode film layer can be tested by methods known in the art. As an example, take the coated positive electrode sheet, punch it into a small disc with an area of S1, weigh it, and record it as M1. Then wipe off the positive electrode film layer of the weighed positive electrode sheet, weigh the weight of the positive electrode collector, and record it as M0. The coating surface density of the positive electrode film layer = (M1-M0) / S1.
[0103] The high coating surface density of the positive electrode film is beneficial to improving the energy density of the battery. At the same time, the aforementioned multi-layer design can also solve the technical problem of poor wettability of the inner layer of the film due to the large surface density, thereby improving the cycle performance and storage performance of high energy density batteries.
[0104] In some embodiments, the first region further includes a first conductive agent and a first adhesive.
[0105] In some embodiments, the second region further includes a second conductive agent and a second adhesive.
[0106] In some embodiments, the first conductive agent and the second conductive agent may independently include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0107] In some embodiments, the first binder and the second binder may independently include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.
[0108] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector.
[0109] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0110] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0111] In some embodiments, the method for preparing the positive electrode film layer includes: coating a first positive electrode slurry containing a first active material, a first conductive agent, and a first binder on a current collector, and drying to obtain a first region and a portion of a middle region of the positive electrode film layer;
[0112] A second positive electrode slurry containing a second active material, a second conductive agent and a second binder is coated on the above-mentioned part of the middle region, and dried to obtain the remaining middle region and the second region of the positive electrode film layer.
[0113] In some embodiments, the first positive electrode slurry may further include a first oxide.
[0114] In some embodiments, the second positive electrode slurry may further include a second oxide.
[0115] In some embodiments, the method for preparing the positive electrode film layer includes: using a dual-chamber coating device to extrude a first positive electrode slurry and a second positive electrode slurry at the same time, coating the second slurry on the first slurry, and drying to obtain the positive electrode film layer.
[0116] [Negative electrode]
[0117] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0118] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0119] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0120] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0121] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0122] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0123] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0124] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0125] [Electrolytes]
[0126] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid or gel.
[0127] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0128] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0129] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0130] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0131] [Isolation film]
[0132] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0133] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0134] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0135] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0136] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0137] [Secondary battery]
[0138] In one embodiment of the present application, a secondary battery is provided, comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, wherein the binder in the active material layer of the positive electrode sheet comprises the polymer of any embodiment of the present application.
[0139] In some embodiments, the secondary battery is a lithium ion battery or a sodium ion battery. During the battery charge and discharge process, active ions are inserted and removed back and forth between the positive electrode and the negative electrode. The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The separator is arranged between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0140] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0141] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0142] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0143] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 4 The secondary battery 5 is a square structure as an example.
[0144] In some embodiments, reference Figure 5 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0145] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0146] Figure 6 4 is an example of a battery module. Figure 6 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0147] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0148] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0149] Figure 7 and Figure 81 is a battery pack 1 as an example. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0150] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0151] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0152] Fig. 9 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0153] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0154] Example
[0155] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0156] 1. Preparation method
[0157] Example 1
[0158] 1) Preparation of positive electrode
[0159] The first active material carbon-coated lithium iron phosphate (A1) (volume distribution particle size Dv50 is 1.0 μm, BET is 13 m 2 / g, the mass content of the carbon layer is 3%), the conductive agent carbon black Super P, and the binder polyvinylidene fluoride are fully stirred and mixed in a proper amount of solvent N-methylpyrrolidone in a weight ratio of 96:1.5:2.5 to form a first slurry.
[0160] The second active material carbon-coated lithium iron phosphate (B1) (volume distribution particle size Dv50 is 1.1 μm, BET is 12 μm 2 / g, the mass content of the carbon layer is 1%), the conductive agent carbon black Super P, and the binder polyvinylidene fluoride are fully stirred and mixed in a proper amount of solvent N-methylpyrrolidone in a weight ratio of 96:1.5:2.5 to form a second slurry.
[0161] The first slurry and the second slurry are extruded simultaneously through a double-chamber coating device. The first slurry is coated on the positive electrode current collector copper foil, and the second slurry is coated on the first slurry; after drying and cold pressing, the positive electrode sheet is obtained. The coating surface density of the first slurry and the second slurry is 0.160g / 1540.25mm 2 and 0.160g / 1540.25mm 2 The coating surface density of the positive electrode film is 0.320g / 1540.25mm 2 .
[0162] 2) Preparation of negative electrode sheet
[0163] The negative electrode material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber, and the thickener sodium carboxymethyl cellulose are fully stirred and mixed in a proper amount of solvent deionized water at a mass ratio of 96:1:2:1 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.
[0164] 3) Isolation film
[0165] Polyethylene is used as the separator.
[0166] 4) Preparation of electrolyte
[0167] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L.
[0168] 5) Preparation of batteries
[0169] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, and a battery cell is obtained after winding. The battery cell is placed in an outer package, and the above-mentioned electrolyte is added. After packaging, standing, forming, aging and other processes, a secondary battery is obtained.
[0170] Embodiment 2-4
[0171] The difference between Example 2-4 and Example 1 is that the first active material carbon-coated lithium iron phosphate (A1) is replaced by A2-A4. See Table 2 for specific parameters.
[0172] Example 5
[0173] Compared with Example 1, the difference is that the preparation method of the first slurry is adjusted, as follows:
[0174] The first active material carbon-coated lithium iron phosphate (A1), inorganic metal oxide Al2O3, conductive agent carbon black SuperP, and binder polyvinylidene fluoride are fully stirred and mixed in an appropriate amount of solvent N-methylpyrrolidone in a weight ratio of 95.910%:0.090%:1.5%:2.5% to form a first slurry, wherein the mass content of inorganic metal oxide Al2O3 is 0.094%, based on the total mass of carbon-coated lithium iron phosphate (A1) and inorganic metal oxide.
[0175] Example 6
[0176] Compared with Example 5, the difference is that the preparation methods of the first slurry and the second slurry are adjusted, as follows:
[0177] The first active material carbon-coated lithium iron phosphate (A1), the conductive agent carbon black Super P, and the binder polyvinylidene fluoride are fully stirred and mixed in a proper amount of solvent N-methylpyrrolidone at a weight ratio of 96%:1.5%:2.5% to form a first slurry.
[0178] The second active material carbon-coated lithium iron phosphate (B1), inorganic metal oxide Al2O3, conductive agent carbon black SuperP, and binder polyvinylidene fluoride are fully stirred and mixed in an appropriate amount of solvent N-methylpyrrolidone in a weight ratio of 95.910%:0.090%:1.5%:2.5% to form a second slurry, wherein the mass content of inorganic metal oxide Al2O3 is 0.094%, based on the total mass of carbon-coated lithium iron phosphate (B1) and inorganic metal oxide.
[0179] Embodiment 7-15
[0180] Compared with Example 5, Examples 7-15 adjust the type of inorganic oxide in the first slurry and the mass ratio of the inorganic oxide in the first slurry, as shown in Table 1:
[0181] Table 1
[0182]
[0183]
[0184] Examples 16-20 adjust the volume distribution particle size Dv50 and specific surface area of the first active material carbon-coated lithium iron phosphate. See Table 5 for specific parameters.
[0185] Embodiment 21
[0186] The difference between Example 21 and Example 1 is that the preparation method of the positive electrode sheet is adjusted, which is as follows:
[0187] The first active material carbon-coated lithium cobalt oxide (volume distribution particle size Dv50 is 15.0 μm, BET is 0.31 μm) 2 / g, the mass content of the carbon layer is 2%), the conductive agent carbon black Super P, and the binder polyvinylidene fluoride are fully stirred and mixed in a proper amount of solvent N-methylpyrrolidone in a weight ratio of 97%:1.5%:1.5% to form a first slurry.
[0188] The second active material is lithium cobalt oxide (volume distribution particle size Dv50 is 14.8 μm, BET is 0.19 μm 2 / g), conductive agent carbon black (Super P), and binder polyvinylidene fluoride are fully stirred and mixed in a proper amount of solvent N-methylpyrrolidone in a weight ratio of 97%:1.5%:1.5% to form a second slurry.
[0189] The first slurry and the second slurry are extruded simultaneously through a double-chamber coating device. The first slurry is coated on the positive electrode current collector copper foil, and the second slurry is coated on the first slurry; after drying and cold pressing, the positive electrode sheet is obtained. The coating weight of the first slurry and the second slurry are 0.161g / 1540.25mm 2 and 0.161g / 1540.25mm 2 The coating surface density of the positive electrode film is 0.322g / 1540.25mm 2 .
[0190] Examples 22-23
[0191] Compared with Example 1, the difference between Examples 22-23 is that the coating surface density of the first slurry and the second slurry is adjusted, thereby adjusting the coating surface density of the positive electrode film layer, as follows:
[0192] Example 22: The coating weights of the first slurry and the second slurry are 0.130 g / 1540.25 mm 2 and 0.130g / 1540.25mm 2 The coating surface density of the positive electrode film is 0.260g / 1540.25mm 2 .
[0193] Example 23: The coating weights of the first slurry and the second slurry are 0.225 g / 1540.25 mm 2 and 0.225g / 1540.25mm 2 The coating surface density of the positive electrode film is 0.450g / 1540.25mm 2 .
[0194] Comparative Example 1
[0195] Compared with Example 1, the preparation method of the positive electrode sheet is adjusted, as follows:
[0196] Carbon-coated lithium iron phosphate (volume distribution particle size Dv50 is 1.1 μm, BET is 12 μm 2 / g, the mass content of the carbon layer is 1%), conductive agent carbon black Super P, and binder polyvinylidene fluoride are fully stirred and mixed in a proper amount of solvent N-methylpyrrolidone according to a weight ratio of 96:1.5:2.5 to form a positive electrode slurry, and the positive electrode slurry is coated on the positive electrode collector copper foil, and after drying and cold pressing, a positive electrode sheet is obtained.
[0197] Comparative Example 2
[0198] Compared with Example 1, the difference lies in the coating position of the first slurry and the second slurry. The second slurry prepared in Example 1 is coated on the positive electrode current collector aluminum foil, and the first slurry prepared in Example 1 is coated on the second slurry prepared in Example 1; after drying and cold pressing, the positive electrode sheet is obtained.
[0199] Comparative Example 3
[0200] Compared with Example 21, the preparation method of the positive electrode sheet is adjusted, as follows:
[0201] Lithium cobalt oxide (volume distribution particle size Dv50 is 14.8 μm, BET is 0.19 μm 2 / g), conductive agent carbon black Super P, and binder polyvinylidene fluoride are fully stirred and mixed in a proper amount of solvent N-methylpyrrolidone at a weight ratio of 97:1.5:1.5 to form a positive electrode slurry, and the positive electrode slurry is coated on the positive electrode collector copper foil, and after drying and cold pressing, a positive electrode sheet is obtained.
[0202] Comparative Example 4
[0203] Compared with Example 21, it can be seen that the difference lies in the coating position of the first slurry and the second slurry. The second slurry prepared in Example 21 is coated on the positive electrode current collector aluminum foil, and the first slurry prepared in Example 21 is coated on the second slurry prepared in Example 21; after drying and cold pressing, the positive electrode sheet is obtained.
[0204] 2. Test Method
[0205] 1. Test method for average discharge specific capacity of active materials
[0206] At 25°C, the secondary batteries in Examples 1-20, 22-23 and Comparative Example 1-2 were charged at a constant current of 0.33C to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current of 0.05C, and after standing for 5 minutes, the secondary batteries were discharged at a constant current of 0.33C to a voltage of 2.5V. The discharge capacity is the first cycle discharge capacity of the secondary battery. The capacity divided by the total mass of the first positive electrode active material and the second active material in the battery is the average discharge specific capacity of the battery.
[0207] 2. Cyclic performance at high temperature
[0208] At 60°C, the secondary batteries in Examples 1-20, 22-23 and Comparative Example 1-2 were charged at 1C constant current to a voltage of 3.65V, then charged at 3.65V constant voltage to a current of 0.05C. After standing for 5 minutes, the battery was discharged at 1C constant current to a voltage of 2.5V. This is a charge and discharge process, and the discharge capacity C0 of the first cycle is recorded. According to this method, the battery was charged and discharged for 1000 cycles, and the battery capacity after 1000 cycles was recorded as C1. The cycle capacity retention rate of the battery at 60°C = C1 / C0*100%. The higher the capacity retention rate under the above test conditions, the better the high temperature cycle performance.
[0209] At 45°C, the secondary batteries in Example 21 and Comparative Examples 3-4 were charged at 1C constant current to a voltage of 4.48V, then charged at 4.48V constant voltage to a current of 0.05C. After standing for 5 minutes, the battery was discharged at 1C constant current to a voltage of 3.0V. This is a charge and discharge process, and the discharge capacity C0 of the first cycle is recorded. According to this method, the battery was charged and discharged for 1000 cycles, and the battery capacity after 1000 cycles was recorded as C1. The cycle capacity retention rate of the battery at 45°C = C1 / C0*100%. The higher the capacity retention rate under the above test conditions, the better the high temperature cycle performance.
[0210] 3. Storage performance at high temperature
[0211] In an environment of 25°C, a charge and discharge test was carried out. The secondary batteries in Examples 1-20, 22-23 and Comparative Example 1-2 were charged at a constant current of 0.33C to a voltage of 3.65V, and then charged at a constant voltage of 3.65V to a current of 0.05C. After standing for 5 minutes, the batteries were discharged at a constant current of 0.33C to a voltage of 2.5V. This is a charge and discharge process, and the discharge capacity of the first cycle is recorded, that is, the initial discharge capacity, recorded as C0. Then, the fully charged battery cell was placed in a 60°C environment for 30 days and then taken out. In a 25°C environment, the battery was first discharged to 2.5V at a rate of 0.33C, and after standing for 5 minutes, it was charged at a constant current of 0.33C to a voltage of 3.65V. Then, it was charged at a constant voltage of 3.65V to a current of 0.05C, and after standing for 5 minutes, the battery was discharged at a constant current of 0.33C to a voltage of 2.5V, and the discharge capacity C1 was recorded. The high-temperature storage capacity retention rate = C1 / C0*100%. The higher the capacity retention rate under the above test conditions, the better the high-temperature storage performance.
[0212] In an environment of 25°C, a charge and discharge test was performed. The secondary batteries in Example 21 and Comparative Examples 3-4 were charged at a constant current of 0.33C to a voltage of 4.48V, and then charged at a constant voltage of 4.48V to a current of 0.05C. After standing for 5 minutes, the battery was discharged at a constant current of 0.33C to a voltage of 3.0V. This was a charge and discharge process. The discharge capacity of the first cycle was recorded, which was the initial discharge capacity, recorded as C0. The fully charged battery cell was then placed in an environment of 60°C for 30 days and then taken out. In an environment of 25°C, the battery was first discharged at a rate of 0.33C to 3.0V. After standing for 5 minutes, the battery was charged at a constant current of 0.33C to a voltage of 4.48V, and then charged at a constant voltage of 4.48V to a current of 0.05C. After standing for 5 minutes, the battery was discharged at a constant current of 0.33C to a voltage of 3.0V. The discharge capacity C1 was recorded. The high temperature storage capacity retention rate = C1 / C0*100%. The higher the capacity retention rate under the above test conditions, the better the high-temperature storage performance.
[0213] III. Analysis of test results of various embodiments and comparative examples
[0214] Secondary batteries of various embodiments and comparative examples were prepared according to the above method, and various parameters were measured. The results are shown in the following table.
[0215] Table 2
[0216]
[0217] Table 3
[0218]
[0219] It can be seen from Tables 2 and 3 that the first active material in the first region of the positive electrode plate of the present application includes a lithium iron phosphate or lithium cobalt oxide matrix material and a first carbon layer coated on the surface of the lithium iron phosphate or lithium cobalt oxide matrix material, and the second active material in the second region includes a lithium iron phosphate or lithium cobalt oxide matrix material and a second carbon layer coated on the surface of the lithium iron phosphate or lithium cobalt oxide matrix material, wherein the mass content of the first carbon layer in the first active material is greater than the mass content of the second carbon layer in the second active material.
[0220] From the comparison between Examples 1, 22-23 and Comparative Examples 1-2, and between Example 21 and Comparative Examples 3-4, it can be seen that controlling the mass content of the first carbon layer in the first active material to be greater than the mass content of the second carbon layer in the second active material can increase the high-temperature cycle capacity retention rate and high-temperature storage capacity retention rate of the battery, and improve the cycle and storage performance of the battery.
[0221] It can be seen from Examples 1-4 that when the mass content of the first carbon layer in the first active material is 2%-4%, the battery has a high high-temperature cycle capacity retention rate and a high-temperature storage capacity retention rate, and the battery has excellent storage and cycle performance.
[0222] Table 4
[0223]
[0224]
[0225] From the comparison between Examples 5-15 and Example 1, it can be seen that the first region and / or the second region contains a first oxide or a second oxide of Al2O3, MgO, TiO2, ZrO2, Y2O3 or CaO, which can improve the high-temperature cycle capacity retention rate and high-temperature storage capacity retention rate of the battery and improve the cycle and storage performance of the battery.
[0226] From the comparison between Example 5 and Example 6, it can be seen that controlling the mass content of the first oxide in the first region to be X% greater than the mass content of the second oxide in the second region to be Y%, improves the high temperature cycle and storage capacity retention rate of the battery, which is conducive to obtaining a long-life battery with high energy density.
[0227] Table 5
[0228]
[0229] From the comparison between Examples 5, 17-20 and Example 16, it can be seen that the volume distribution particle size Dv50 of the first active material of the carbon-coated lithium iron phosphate is 0.5μm-2.0μm, which can improve the high-temperature cycle capacity retention rate and high-temperature storage capacity retention rate of the battery and improve the cycle and storage performance of the battery.
[0230] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, comprising a positive electrode plate, characterized in that: The positive electrode plate includes a positive electrode current collector and a positive electrode film layer formed on at least one surface of the positive electrode current collector, the positive electrode film layer has a first surface away from the positive electrode current collector and a second surface arranged opposite to the first surface, the thickness of the positive electrode film layer is recorded as H, the area within the thickness range from the second surface of the positive electrode film layer to 0.1H is recorded as the first area of the positive electrode film layer, and the area within the thickness range from the first surface of the positive electrode film layer to 0.1H is recorded as the second area of the positive electrode film layer, the first area includes a first active material, and the second area includes a second active material, the first active material includes a first matrix material and a first carbon layer coated on the surface of the first matrix material, the second active material includes a second matrix material and a second carbon layer coated on the surface of the second matrix material, and the mass content of the first carbon layer in the first active material is greater than the mass content of the second carbon layer in the second active material.
2. The secondary battery according to claim 1, characterized in that: The mass content of the first carbon layer in the first active material is 2%-4%.
3. The secondary battery according to claim 1 or 2, characterized in that: The mass content of the second carbon layer in the second active material is 0%-1.9%.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The first region includes a first oxide, and the second region includes a second oxide, wherein the first oxide and the second oxide each independently include one or more of Al2O3, MgO, TiO2, ZrO2, Y2O3, CaO, MnO2, and NiO, The secondary battery satisfies: X%>Y%, Wherein, X% is the mass content of the first oxide, based on the total mass of the first active material and the first oxide in the first region; Y% is the mass content of the second oxide based on the total mass of the second active material and the second oxide in the second region.
5. The secondary battery according to claim 4, characterized in that: The mass content X% of the first oxide is 0.030%-1.0% based on the total mass of the first active material and the first oxide in the first region.
6. The secondary battery according to claim 4, characterized in that: The mass content X% of the first oxide is 0.03%-0.6% based on the total mass of the first active material and the first oxide in the first region.
7. The secondary battery according to any one of claims 4 to 6, characterized in that: The mass content Y% of the second oxide is 0% to 0.5% based on the total mass of the second active material and the second oxide in the second region.
8. The secondary battery according to any one of claims 4 to 6, characterized in that: The mass content Y% of the second oxide is 0% to 0.3% based on the total mass of the second active material and the second oxide in the second region.
9. The secondary battery according to any one of claims 4 to 8, characterized in that: The mass ratio of the sum of the mass of the first active material and the first oxide to the sum of the mass of the second active material and the second oxide is 1:9-9:
1.
10. The secondary battery according to any one of claims 1 to 9, characterized in that: The first matrix material and the second matrix material each independently include one or more of a layered oxide material, a spinel lithium manganate material, a phosphate material, and modified forms of any of the foregoing substances, wherein the modified forms include one or more of doping modification and coating modification.
11. The secondary battery according to any one of claims 1 to 10, characterized in that: The first matrix material and the second matrix material both include lithium iron phosphate.
12. The secondary battery according to claim 11, characterized in that: The volume distribution particle size Dv50 of the first active material is 0.5 μm-2.0 μm; and / or the volume distribution particle size Dv50 of the second active material is 0.5 μm-2.0 μm.
13. The secondary battery according to claim 11, characterized in that: The volume distribution particle size Dv50 of the first active material is 0.8 μm-1.5 μm; and / or the volume distribution particle size Dv50 of the second active material is 0.8 μm-1.5 μm.
14. The secondary battery according to any one of claims 11 to 13, characterized in that: The specific surface area of the first active material is 8 m 2 / g-16m 2 / g; and / or, the specific surface area of the second active material is 9m 2 / g-15m 2 / g.
15. The secondary battery according to any one of claims 11 to 14, characterized in that: The mass content of the second carbon layer in the second active material is 0.5%-1.9%.
16. The secondary battery according to any one of claims 11 to 14, characterized in that: The mass content of the second carbon layer in the second active material is 0.7%-1.7%.
17. The secondary battery according to any one of claims 1 to 16, characterized in that: The coating surface density of the positive electrode film layer is 0.26g / 1540.25mm 2 -0.45g / 1540.25mm 2 .
18. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 17.
Citation Information
Patent Citations
Lithium ion battery
CN111326728A
Positive plate with special-shaped structure and lithium ion battery comprising positive plate
CN111969214A
Positive plate and lithium ion battery
CN113871572A
Positive plate and preparation method thereof, electrode assembly, battery monomer, battery and electric equipment
CN115832182A
Surface-coated layered oxide and preparation method thereof, positive plate, sodium ion battery and electric equipment
CN116143199A